2004
DOI: 10.1177/039139880402700609
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Engineered Acellularized Valve Xenografts: A Comparative Animal Study between Plain Acellularized Xenografts and Autologous Endothelial Cell Seeded Acellularized Xenografts

Abstract: Background Acellularized valve xenografts are considered a promising way of overcoming the inherent limitations of current prosthetic valves. The aim of this study was to compare the biological responses of an autologous endothelial cell seeded acellularized xenograft (AAX) and a plain acellularized xenograft (PAX) implanted in the pulmonary valve leaflet in the same animal. Methods Endothelial cells were isolated and cultured from the jugular vein of goats. Porcine valve leaflets were acellularized with Nac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…For the tissue engineering of heart valves or vessels, several different strategies have been considered in the use of biodegradable scaffolds or decellularized biological scaffolds seeded with the cellular tissue component either in vitro or in vivo (6–10). The major disadvantages of in vitro seeding with autologous cells are additional surgical invasion and the complicated nature of the process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the tissue engineering of heart valves or vessels, several different strategies have been considered in the use of biodegradable scaffolds or decellularized biological scaffolds seeded with the cellular tissue component either in vitro or in vivo (6–10). The major disadvantages of in vitro seeding with autologous cells are additional surgical invasion and the complicated nature of the process.…”
Section: Discussionmentioning
confidence: 99%
“…So far, Leyh et al demonstrated in a sheep model that plain decellularized porcine valve matrix conduits were repopulated in vivo with valve‐specific cell characterization in the pulmonary circulation (9). Kim et al reported in a goat model that plain decellularized porcine valve leaflets with or without seeding of autologous endothelial cells (ECs) in vitro showed similar biological reactions concerning cell characterization and antithrombogenicity in the pulmonary circulation (10). However, the role and necessity of autologous cell seeding remain controversial (8–10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An ideal scaffold should help to retain cells in the desired location and provide appropriate biochemical signals in the same way as the natural ECM for which it substitutes. A variety of decellularized tissues including ligaments, heart valves, blood vessels, skin, nerves, and urinary bladder have been investigated for tissue engineering applications. A DCM‐derived scaffold has been successfully developed and used for cartilage tissue engineering.…”
Section: The Rationale For Our Hypothesismentioning
confidence: 99%